Hot rolling of the superaustenitic stainless steel AISI 904L - Tehovnik, Franc (Materiali in tehnologije, 2014)
The AISI 904L superaustenitic stainless steel has a narrow processing window. In this work the hot rolling of steel, specifically the hot deformation behavior, is investigated. Specimens of steel were hot rolled at temperatures from 1000 °C to 1250 °C with 50 °C increments and the rolling loads were measured and recorded. Microstructural changes were examined, with the accent on the recrystallization. From changes of the hot-rolling loads and microstructure it is concluded that the recrystallization begins at temperatures around 1050 °C and three passes of 20 % deformation at the deformation rate of 5 s-1. In order to avoid over loads of rolling stand at equal deformation rate and degree, the recommended temperature was 1100 °C. The upper hot-working temperatures were not as clearly determined, it is considered to be around 1250 °C.
Keywords: hot rolling; vroče valjanje; superaustenitic stainless steel; superavstenitno nerjavno jeklo; microstructure; mikrostruktura; segregacija; segregation bands